Beyond Vibranium: Revealing Power Dynamics in Black Panther: ‘Wakanda Forever’ Movie (2022) - Jacobus, Benaiya Tristan; Manullang, Petronio Pirdon; Setiawan, Steven Febryan; Tan, Emmanuel; Noah, Abimanyu; Maukary, Brandon Ezra (Jurnal Pendidikan Makarios, 2024)
This study aims to show how power operates through knowledge and control, which plays out in the movie "Black Panther: Wakanda Forever (2022)," for its precious source, vibranium. Employing the analytical framework by Foucault's theory of Power: Discipline and Punish: The Birth of the Prison (1977). The analysis unveils a perspective towards ‘isolation vs global responsibility’ exploring deeply into the details of the movie. The visual effects and the cameraworks of the cinematography and the selected utterances were also conveyed along with the analysis of the movie. As a result: 1) The movie depicts Wakanda's view of vibranium as a global responsibility, aligning with Foucault's idea of power permeating the entire social body. 2) Wakanda's efforts to protect vibranium triggers the exercise of sovereign power, reflecting the centralized control over valuable resources. 3) The tension between ‘isolation’ and ‘global responsibility’, with Queen Ramonda resulting in refusal to trade vibranium due to its dangers and ethical concerns about sharing advanced technology for power abuse. The power dynamics in Wakanda help shape the identity and decision-making. The analysis of the issue of power dynamics of isolation, global responsibility in the movie leads to the insight and understanding about the ethics of sharing technology that provide rich material for a better good.